MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN MENGANYAM PADA ANAK USIA 5–6 TAHUN DI TK IRSYADUL UMMAH KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Nurlin Fauzi; Daviq Chairilsyah; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims 1) To determine whether the weaving activity can improve fine motor skills of children aged 5-6 years in TK Irsyadul Ummah Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi. 2) To find out how to increase the fine motor skills of children aged 5-6 years through weaving. 3) To know how much improvement the fine motor skills of children aged 5-6 years after weaving activities. This research is a classroom action research. According Suharsimi et al (2006) classroom action research (PTK) is the research done in the classroom in order to improve or enhance the quality of teaching practices. The research sample is the child Class B consisting of 18 children consisted of 8 boys and 10 girls. Collecting data using observation and documentation. Based on the survey results revealed that 1) the fine motor skills of children aged 5-6 years in TK Irsyadul Ummah Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi before weaving activities berkriteria least once in the classical meaning of fine motor skills of children undeveloped. After weaving activity in cycle I and II in the classical meaning berkriteria either generally or fine motor skills the child has developed very well. 2) The braiding can improve fine motor skills of children aged 5-6 years in TK Irsyadul Ummah Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi. 3) fine motor skills of children aged 5-6 years in TK Irsyadul Ummah Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi increased in every cycle, namely the pre-cycle to the first cycle there is an increase of 46.7%. Improved fine motor cycle I to cycle II of 34.1%, and the overall improvement of fine motor prasiklus to cycle II of 96.7%. This is due to the increasing creativity of teachers in selecting media and learning activities mennganyam to improve fine motor skills of childrenKeywords: weaving activities, fine motor